Renforcement par clouage et soutenement d’un versant naturel instable urbanise. - Zouleykha, Djeffal (University of M'sila, 2014)
The purposeo fthe work presentedin this memoryi s to analyses tability of landslide. The first part is a literature review on methods for analyzing the stability of slopes and stabilization techniquesf or reinforeement.Andit is containsa numerical modeling using the software TALREN version 4 and the code of finite element PLAXIS.This model consists of comparative analysis of calculationr esultso f safetyf actor to slipping by different methodsw ith implementationo f the algerian para-sesmicc ode. The second part is a pratical application to the study of stability and stabilization of an embakment reinforcementlo cateda tTiziN'Bechar(wilaya of setif) in algeria